Understanding the interfacial behavior in isopycnic Lennard-Jones mixtures by computer simulations. Issue 2 (11th December 2015) - Garrido, José Matías; Piñeiro, Manuel M.; Mejía, Andrés; Blas, Felipe J.
Abstract : Singular structures of total density profiles under molar isopycnicity conditions. Abstract : The physical characterization of the singular interfacial behavior of heterogeneous fluid systems is a very important step in preliminary stages of the design process, and also in the subsequent procedures for the determination of the optimal operating conditions. Molar isopycnicity or molar density inversion is a special case of phase equilibrium behavior that directly affects the relative position of phases in heterogeneous mixtures, without being affected by gravitational fields. This work is dedicated to characterize the impact of molar density inversion on the interfacial properties of Lennard-Jones binary mixtures. The results and specific trends of the molar density inversion phenomena on the peculiar calculated composition profiles across the interface and interfacial tensions are explored by using canonical molecular dynamics simulations of the Lennard-Jones binary mixtures. Our results show that the density inversion causes drastic changes in the density profiles of the mixtures. In particular, symmetrical and equal-sized Lennard-Jones mixtures always exhibit desorption along the interfacial zone, i.e. the interfacial concentration profiles show a relative minimum at the interface of the total density profiles that increases when the dispersive energy parameter ( ε ij ) between unlike species decreases. However, as the asymmetry of the Lennard-Jones mixtures increases ( σ i ≠ σ j ), the concentration profiles display a relative maximum at the interface, which implies the adsorption of the total density profiles along the interfacial zone.